Review of recent publications (Studies in 20th & 21st Century Literature, 2012)
Christine Daigle. Jean-Paul Sartre by Candice Nicolas Anna Marie Sandoval. Toward a Latina Feminism of the Americas: Repression and Resistance in Chicana and Mexicana Literature by Yajaira M. Padilla Ruth Cruickshank. Fin de millénaire French Fiction: The Aesthetics of Crisis by Martine Motard-Noar Sanna Turoma. Brodsky Abroad: Empire, Tourism, Nostalgia by Galya Diment Svetlana Alexievich. Voices from Chernobyl: the Oral History of a Nuclear Disaster by Teresa Polowy Leslie Raymond Williams. A Companion to Gabriel García Márquez by David William Foster
Keywords: Jean-Paul Sartre; Candice Nicolas; Latina Feminism; repression; Resistance; Chicana Literature; Mexicana Literature; Yajaira M. Padilla; French Fiction; Aesthetics of Crisis; Martine Motard-Noar; Empire; Tourism; Nostalgia; Galya Diment; Chernobyl; Oral History; Nuclear Disaster; Teresa Polowy; Gabriel García Márquez; David William Foster